Manufacturing The Enemy: An Analysis of the Media’s Villainization of Arabs and Framing Tactics - Oumari, Sama (Canadian Journal for the Academic Mind, 2025)
The consistency of our values and perceptions are reinforced daily by the media we consume. The way in which a piece of media is framed can entirely shift one’s perspective. In the case of villainization, the framing of a news article can push someone away from a cause and entirely dismiss it, or draw them in by capturing their sense of care. The media has captured and controlled many of our ideologies, promoting them as the ‘correct’ way of thinking. This plays an integral role in societal perceptions of the Middle East.What comes to mind when one hears Syria, Iraq and Afghanistan, and why do negative connotations come to mind? This article will explore how Western media has painted minority groups as villains throughout the years to support hegemonic global power and influence.